Research on policy instruments for promoting green lifestyle in China—a multi-dimensional analysis based on current policy texts - Tian, Huawen; Cui, Yan; Dong, Jian (Frontiers in Environmental Science, 2024)
Over the past decade, the construction of an ecological civilization has emerged as a prominent national strategy in China. Commencing in 2020, the Chinese government formally introduced the objectives of peaking carbon dioxide emissions before 2030 and achieving carbon neutrality before 2060. The promotion of green lifestyles is not only an important topic but also serves as the foundation and crucial starting point for realizing the construction of an ecological civilization. It is also an indispensable pathway towards achieving the goals of "carbon peaking and carbon neutrality". Therefore, the current progress of China's efforts in this domain undoubtedly merits attention, the purpose of this study is to elaborate this issue. From the theoretical perspective of policy instruments, text analysis methods were used to encode 92 policy texts of research value promulgated by the Chinese government. Based on an analysis of three dimensions-the categories of policy instruments, the target groups affected by these instruments, and the entities responsible for implementing them-the following conclusions can be drawn regarding the promotion of green lifestyles in China. Currently, the promotion primarily relies on information-based instruments and market-based instruments, with some supplementation from coercive instruments. Information-based instruments are predominantly employed for the general public, whereas a combination of market-based, information-based, and coercive instruments is utilized for production enterprises. However, there are certain deficiencies in the attention given by local governments to this issue, which is reflected in the limited number of policy instruments adopted by them, their singular focus, and the lack of constraints on enterprises. Overall, the current selection of policy instruments is reasonable. However, there are also notable issues that need to be addressed. These include an over-reliance on information-based instruments, inadequate stimulation of market-based instruments, and too little use of voluntary instruments.